Efficiency of Self-Management Technique as a Therapy to Improve Students' Learning Discipline: Literature Review - Widia Sri Haryani; Ibnu Maulana; Denata Viana da Conceicão; Telma Joana Corte Real de Oliveira (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Discipline in school is important to be applied to students to form a person who is responsible, independent, and able to regulate and control their behavior. The purpose of this study was to determine the efficiency of self-management techniques as a therapy to improve student learning discipline through a literature review. This research used a systematic literature review. systematic literature review. The process of collecting data through article screening. The data that will be presented in this study are tabular from the results of related research journals in accordance with the research variables of the literature review approach. The results showed that self-management techniques can be used in improving student learning discipline. The results of previous research reveal that self-management techniques are an effective approach in improving student learning discipline at various levels of education and learning contexts.